Preparation of glass material and its physical properties / Azman Kasim, Nurbaisyatul Ermiza and Wan Aizuddin Wan Razali - Kasim, Azman; Ermiza, Nurbaisyatul; Wan Razali, Wan Aizuddin (2011)
Glass is an amorphous material that could be prepared by using variety of techniques. The most well known and practically used methods are sol-gel and melt-quenched techniques. In most research work, the melt-quenched technique has been widely used and the techniques will be discussed in details in this report. This paper will explains the research methodology of the overall experimental procedure which includes the materials selection, weighing process, powder mixing, milling process, melting process, annealing and cooling process. Some explanation on the measuring of the basic physical properties also will be given. In this works, series of glass samples have been successfully prepared at the Glass Preparatory Lab., UiTM Good quality of glass sample has been obtained as a result of the proper standard procedure of glass preparation. The glass sample has then undergone certain measurement in term of their physical properties. The data has been analysed and discussed.